Changes in the microbial population during storage of the smoked fish, Amhlypharyngodon mola of Manipur - Lilabati, H; Viswanath, W (Indian Journal of Fisheries, 2011)
Changes in the total plate counts of bacteria (TPC), fungi (TFC), coliform andpathogenic bacteria viz, Escherichia coli, Salmonella, Staphylococcus aureus andfaecal Streptococci, and the fungal flora during storage of smokeA Amhlypharyngodonmola were studied. There was a strong relationship between the microbial countsand meteorological data during the storage. In the samples of monsoon, summerand winter, fungal colonies were visible respectively on the 75th, 90th and 105thday. TFC was highest in monsoon season. In all the seasons, coliform,Staphylococcus aureus and faecal Streptococci were detected in the beginning ofthe storage, which gradually reduced and vanished. The seasons in which coliformsappeared for the longest duration was summer (15 days). Staphylococcus aureus,monsoon (45 days), faecal Streptococci, winter (60 days.) E. coli. and Salmonellawere not detected in all the seasons. Aspergillus niger, Penicillium funiculosum,Trichoderma longibranchiatum and Aspergillus flavipes were dominant inmonsoon; A. niger, Penicillium funiculosum and Cladosporium cladosporoids inwinter and A. niger, A. repens and A. flavipes in summer. Of all the seasons, storagelife was shortest in monsoon.